Dimensión subjetiva del trabajo: Algunas ideas a partir de una investigación con profesionales (2013)
This paper presents some ideas about the subjective dimension of work from ethnographic research with two professional groups, one composed of those who are inserted in the labor market before 1990 and another for those who do it later. It is found that there are no radical differences between the two groups in relation to the meaning of work (hobby; activity of the mind; collection of values; challenge; blessing; difficulty, effort, and slavery), which could be related with the fact that the value systems, of which the meanings are a part of remain, prevalent for a long time and seem not to be strongly affected by the restructurings of the labor field.